China's Medium and Long-Term Science and Technology Program - Chen, Zhenghong. author. aut Link
XXI, 237 p. 37 illus., 5 illus. in color.
Keywords: This book conducts a panoramic study on the history of China’s Science and Technology which focuses on the Medium and Long-Term Science and Technology Program (MLSTP). In general these Programs have a duration of 5-30 year. This book provides an epochal assessment of the project’s conceptual context over the past 60 years.. The author shows that the historical evolution and conceptual development of China’s MLSTP are the result of an amalgamation of political, economic and social factors within distinct contemporary contexts. As a national action plan, MLSTP has incorporated many of the factors that go beyond the intentional factors of science and technology. MLSTP is not only a macro vision and blueprint for scientific and technological development; it is also a political act of realizing the national will. While ensuring the MLSTP builds on its great achievements, the author also reflects upon its deficiencies and disadvantages in order to better promote theadvancement of science and technology in China. This book comprehensively lays out the historical and theoretical dimensions. Based on a clear vision of historical constructivism the author has compiled the MLSTP philosophy of different eras into a conceptual framework for this era and used this framework to research and analyze the historical and conceptual evolution of MLSTP. Research on MLSTP is important for as enrichment of contemporary studies in the history of science and the science and technology policy. In 2010, more than 60 years after the establishment of the People’s Republic of China, the country had enacted 10 MLSTP programs. This book separates the development of the MLSTP into three different historical eras: the era of economic planning, the era of economic transformation and the new century. Each historical epoch corresponds to a different MLSTP philosophy concept, which enables usto study the conceptual evolution of MLSTP using historical research as our foundation. .